Planning a trip abroad with a resident. (2nd May 2019) - Ashurst, Adrian
Abstract : A trip abroad is an opportunity to learn and relax and it is important that residents who want to travel are given the opportunity. Adrian Ashurst talks through a case study, setting out what preparations and precautions are needed.